Synergistic Radiosensitization Mediated by Chemodynamic Therapy via a Novel Biodegradable Peroxidases Mimicking Nanohybrid - Zhang, Jun; Jiang, Dazhen; Lyu, Meng; Ren, Shiqi; Zhou, Yunfeng; Cao, Zhen (Frontiers in Oncology, 2022)
Purpose Reactive oxygen species (ROS) are practically essential in radiotherapy to damage cancer cells; however, they are always inadequate for some malignant entities. Here, we designed a biodegradable mesoporous silica decorated with hemin and glucose oxidase (GOD@Hemin-MSN) to generate a chemodynamic therapy in order to enhance the killing capacity of radiotherapy. Methods Mesoporous silica, as an outstanding drug carrier, can deliver hemin and glucose oxidase to the tumor site. With high level of metabolism activity, cancer cells are abundant in glucose, which can be oxidized into H2O2 by glucose oxidase (GOD) on site. The generated H2O2 is subsequently converted into intracellular ROS, especially hydroxyl radical within the tumor microenvironment, by hemin, which has mimetic peroxidase properties. By this means, the ROS can be supplemented or enriched to facilitate the killing of tumor cells. Results The chemodynamic therapy induced by GOD@Hemin-MSN produced quantities of ROS, which compensated for their inadequacy as a result of radiotherapy, and exhibited remarkable antitumor efficacy, with a tumor inhibition rate of 91.5% in A549 tumor-bearing mice. Conclusion This work has validated GOD@Hemin-MSN as a radiosensitizer in chemodynamic therapy, which showed biocompatibility and potential for translational application.